The Effect of Ownership The Effect of Tax Audit, Tax Amnesty and Non-Taxable Income on Income Tax Receipts at the Medan City Pratama Tax Service Office - Fiona HO (Outline Publisher, 2022)
This study aims to determine the effect of Tax Examination, Tax Amnesty and Non-Taxable Income on Income Tax Receipts at Medan City Tax Service Office. The population in this study is the taxpayer registered at the Medan City Tax Service Office. Samples taken from 20 taxpayer using accidental sampling method. The results showed that Tax Examination affected Income Tax Receipts. The results showed that Tax Amnesty affected Income Tax Receipts. The results showed that Non-Taxable Income affected Income Tax Receipts. F test results show that Tax Examination, Tax Amnesty and Non-Taxable Income affected Income Tax Receipts. The results of the coefficient of determination test show that the Income Tax Receipts variables can be explained by Tax Examination, Tax Amnesty and Non-Taxable Income while the remaining Income Tax Receipts variables can be explained by other variable not examined in this study such as Effectiveness of Tax Administration, Taxpayer Awareness, and Taxpayer Compliance.